Methodological Issues in Randomized Clinical Trials for Prodromal Alzheimer's and Parkinson's Disease - Aquino, Camila Henriques de (Frontiers in Neurology, 2021)
Alzheimer’s disease (AD) and Parkinson’s disease (PD) are the first and second most common neurodegenerative disorders, respectively. Both are proteinopathies with an inexorable course and no approved disease-modifying therapy. A substantial effort has been made to identify interventions that could slow down the progression of AD and PD; to date, with no success. The advances in biomarker research improved the identification of individuals at risk for these disorders before symptom onset, recognizing the preclinical stage, in which there is abnormal protein accumulation but no clinical symptoms of the disease, and the prodromal stage, in which mild symptoms are present but the clinical diagnostic criteria for disease cannot be fulfilled. The ability to detect preclinical and prodromal stages of these diseases has encouraged clinical trials for disease-modification at earlier phases, seeking to slow or prevent phenoconversion into clinical disease. Clinical trials at these stages have several challenges, such as the identification of the eligible population, the appropriate choice of biomarkers, the definition of clinical endpoints, the duration of follow-up, and the statistical analysis. This article aims to discuss some of the methodological challenges in the design of trials for preclinical and prodromal phases of AD and PD, to critically review the recent studies, and to discuss methodological approaches to mitigate these challenges in trial design.